«The urbanization of leisure»: private interest and state planning in Mar del Plata (1930-1979) (Estudios Sociales, 2022)
The paper analyses the impact of urban regulations in the conformation of Mar del Plata as a modern city between 1930 and 1979. It explores the relationship between private interest and the role of the State as a strategist in territorial planning of a tourist area. In this line, we stop at the sanctioned legislation and its implementation; the opinion of experts and the professional look in the main magazines of the field; looking finally at the consequences of the official weakness to channel a harmonic building development. We conclude that the "urbanization of leisure" on the coastline was the work of speculative interest in the areas of greatest real estate profitability. And this was guided by private capital together with the consent of the local and provincial State.
Keywords: Mar del Plata; urban plans; State; private capital